PENGUATAN KAPASITAS GURU DALAM MANAJEMEN BERBASIS SEKOLAH: PROGRAM SERVICE LEARNING BERSAMA YAYASAN KAIROS TANAH PAPUA - Yanuard Putro Dwikristanto; Asih Enggar Susanti (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
Kairos Foundation of Tanah Papua is committed to providing quality education access for children in West Papua. The main challenges faced by teachers are the limited training in school management, administration, and effective lesson planning. To address these needs, a service-learning program was carried out through an interactive webinar entitled “Sharing Knowledge and Best Practice Experience.” This activity was based on the reflection of pre-service teachers’ field teaching practice after four months of teaching in schools in Jakarta and its surrounding areas, which was then shared with the teachers. The reflection focused on the implementation of School-Based Management (SBM), including student management, curriculum, leadership, and school facilities management. The program was conducted via the Zoom platform with a participatory and collaborative approach, allowing two-way discussions between pre-service teachers and teachers. The results indicated an increase in teachers’ understanding of the principles and practices of SBM, the development of pre-service teachers’ readiness and confidence to enter the field, as well as the establishment of a commitment to fostering a more contextual, effective, and sustainable school management system. Thus, this program contributes to strengthening the capacity of both teachers and pre-service teachers in realizing quality education toward Indonesia Emas.